The Role of Women Leaders in Increasing Satisfaction Customers at Honda Car Dealers in the Digitalization Era - Christine Indrianny Tanod; Freddy Johanis Rumambi; Larasati Larasati; Marisi Pakpahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This thesis investigates the role of female leaders in enhancing customer satisfaction at Honda car dealers in the digitalization era. As technological advances reshape consumer behaviors and expectations, understanding how female leadership can impact customer experiences in the automotive industry becomes crucial. The research employs a quantitative approach, using surveys to collect data from customers of Honda dealers across various locations. Data analysis involves descriptive statistics and regression techniques to assess the relationship between female leadership styles and customer satisfaction levels. Findings reveal that female leaders often adopt more empathetic and collaborative communication approaches, which positively influence customer experiences. Furthermore, their adaptability to technological changes enhances service delivery and responsiveness to customer needs. The implications of this study highlight the importance of increasing female representation in leadership positions within the automotive sector as a strategy to increase customer satisfaction, particularly in a rapidly evolving digital landscape. This research aims to contribute to the development of human resource management practices and marketing strategies in the automotive industry.